How Not to Make A Megacity. - Goldstein, H. (IEEE spectrum)
Despite Nigeria's enormous oil wealth, tens of billions of dollars have gone missing over the years in this country - one of the world's most corrupt - and few investments have been made in infrastructure. This paper presents environmental, health, political and energy problems the Lagos city of Nigeria is currently experiencing.